A genetically encoded fluorescent sensor for in vivo imaging of GABA - Marvin, Jonathan S; Shimoda, Yoshiteru; Magloire, Vincent; Leite, Marco; Kawashima, Takashi; Jensen, Thomas P; Kolb, Ilya; Knott, Erika L; Novak, Ondrej; Podgorski, Kaspar; Leidenheimer, Nancy J; Rusakov, Dmitri A; et al. (Nature methods, 2019)
Current techniques for monitoring GABA (γ-aminobutyric acid), the primary inhibitory neurotransmitter in vertebrates, cannot follow transients in intact neural circuits. To develop a GABA sensor, we applied the design principles used to create the fluorescent glutamate receptor iGluSnFR. We used a protein derived from a previously unsequenced Pseudomonas fluorescens strain and performed structure-guided mutagenesis and library screening to obtain intensity-based GABA sensing fluorescence reporter (iGABASnFR) variants. iGABASnFR is genetically encoded, detects GABA release evoked by electric stimulation of afferent fibers in acute brain slices and produces readily detectable fluorescence increases in vivo in mice and zebrafish. We applied iGABASnFR to track mitochondrial GABA content and its modulation by an anticonvulsant, swimming-evoked, GABA-mediated transmission in zebrafish cerebellum, GABA release events during interictal spikes and seizures in awake mice, and found that GABA-mediated tone decreases during isoflurane anesthesia.
Keywords: Neurons; záchvaty; Rats; biosenzitivní techniky; potkani Sprague-Dawley; hipokampus; myši inbrední C57BL; mužské pohlaví; mozek; Biosensing Techniques; Mice; molekulární zobrazování; Seizures; anestezie; Animals, Genetically Modified; krysa rodu Rattus; Green Fluorescent Proteins; Brain; ženské pohlaví; zvířata; Zebrafish; geneticky modifikovaná zvířata; dánio pruhované; neurony; zelené fluorescenční proteiny; myši; Anesthesia; Molecular Imaging; Rats, Sprague-Dawley; GABA; gamma-Aminobutyric Acid; Female; Mice, Inbred C57BL; Male; Hippocampus; Animals